MINAT IBU TERHADAP KUNJUNGAN ULANG PIJAT BAYI DI ERA NEW NORMALAbstrak Salah satu Teknik pengobatan yang penting untuk bayi yaitu pijat bayi. Pijat bayi yang dilaksanakan secara rutin akan membantu bayi dalam meningkatkan tumbuh kembangnya dan perkemban - Dwi Ertiana; Dewi Taurisiawati Rahayu; Srilejaring Tiyas (STIKES dan AKZI Karya Husada Kediri, 2022)
One of the important treatment techniques for babies is baby massage. Baby massage that is carried out regularly will help babies to improve their growth and development and their physical and emotional development. In addition, it can also improve the health of the baby. Due to the COVID-19 pandemic, baby massage visits have decreased. The purpose of the study was to describe the mother's interest in repeat visits to infant massage in the new normal era. The research design used is descriptive. Single variable of mother's interest. The research population was mothers who came to Lejar Baby and Kids Spa Malang, amounting to 70 respondents. The research sample was taken by purposive sampling technique, the sample size in this study was 60 respondents. The research instrument used an interest questionnaire. The data analysis used is univariate analysis or descriptive analysis. The study was carried out at Lejar Baby And Kids Spa in October 2021. The results showed that most of the respondents found that out of 60 respondents, most of the respondents (53 respondents) 53.3% had low interest in coming to bring their children for a baby massage during the pandemic in the new era. normal with supporting data most of the respondents (38 respondents) 63.3% rarely visit / bring their children for baby massage. The existence of an unsafe or unhealthy environment with the covid 19 pandemic when the new normal was enacted had an effect on the interest of mothers to come back for baby massage. So that baby massage visits are reduced. Support from various parties is needed, especially support from the closest people, namely family and health workers.